The U.S. Army and the new national security strategy - Davis, Lynn E. (Lynn Etheridge), 1943-; Shapiro, Jeremy (MR (Series) ;, 2003)
How is the U.S. Army changing to fulfill its role in light of the new national security strategy? How must it change further to better accomplish its manifold and varied missions? How did the attacks of September 11, 2001, alter or accelerate the need for change? Is the Army's far-reaching program for change known as the Army Transformation on the right track? Fourteen RAND analysts with broad experience in strategic and Army planning have undertaken to answer these questions. In this book, the authors use nine chapters to examine the Army's role in the offensive war on terrorism; the Army's homeland security needs; the implications for the Army of the increase in emphasis on the Asia-Pacific region; the Army's role in coalition operations; the unfinished business of jointness-the lessons to be learned from recent Army operations and how the Army can better prepare for the future; the Army's deployability, logistical, and personnel challenges; and whether the Army can afford the Transformation as currently envisaged. These chapters are bracketed by a concise introduction, a description of the new national security strategy and the Army's place in it, and a succinct summary of the authors' conclusions. This book is nothing less than a call for the Army to change and a prescription for what needs to be done.